DUAL TRAINING IN HIGHER TECHNICAL EDUCATION IN KAZAKHSTAN - Arstan M. Gazaliyev; Victor V. Egorov; Iosif V. Breydo (Высшее образование в России, 2016)
The article makes an analysis of various world technologies of dual higher education. One of perspective forms of realization of dual higher technical education is using of opportunities of the corporate consortium similar to the consortium created on the basis of the Karaganda state technical university (KSTU). To reduce the terms of study and to except a temporary gap theoretical tutoring should be accomplished on the basis of Internet technologies in an evening form along with getting practical skills and abilities in real industry. The experience of the organization of the distributed education Internet-process in the network modes on technical specialties in KSTU is described.